2023
DOI: 10.1029/2023jc020431
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Equatorial Currents and Tropical Instability Waves During the 2021 Atlantic Niño

Franz Philip Tuchen,
Renellys C. Perez,
Gregory R. Foltz
et al.

Abstract: In the boreal summer of 2021, the equatorial Atlantic experienced the strongest warm event, that is, Atlantic Niño, since the beginning of satellite observations in the 1970s. Such events have far‐reaching impacts on large‐scale wind patterns and rainfall over the surrounding continents. Yet, developing a paradigm of how Atlantic Niño interacts with the upper‐ocean currents and intraseasonal waves remains elusive. Here we show that the equatorial Kelvin wave associated with the onset of the 2021 Atlantic Niño … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…In fact, the 13 TIWs with the largest TIW KE and the 28 most energetic TIWs in terms of ϵ were all observed when Niño 3.4 < 0. Correlations between ϵ and ATL3 (i.e., the sea surface temperature index commonly used to represent the Atlantic Niño; Zebiak, 1993) are also strong and negative at both 23°W and 10°W, consistent with findings of a recent study which showed that TIW occurrence was suppressed during a large Atlantic Niño event (Tuchen et al, 2024). However, a recent study demonstrated that multiyear averaged vertical profiles of ϵ in the ACT and PCT resemble average profiles collected during weekly monthly short-term experiments in the absence of strong TIWs (Moum et al, 2022), implying that TIWs may have a minimal impact on long-term averages.…”
Section: Variability Of Individual Tiws and Relationship With Climate...supporting
confidence: 89%
See 2 more Smart Citations
“…In fact, the 13 TIWs with the largest TIW KE and the 28 most energetic TIWs in terms of ϵ were all observed when Niño 3.4 < 0. Correlations between ϵ and ATL3 (i.e., the sea surface temperature index commonly used to represent the Atlantic Niño; Zebiak, 1993) are also strong and negative at both 23°W and 10°W, consistent with findings of a recent study which showed that TIW occurrence was suppressed during a large Atlantic Niño event (Tuchen et al, 2024). However, a recent study demonstrated that multiyear averaged vertical profiles of ϵ in the ACT and PCT resemble average profiles collected during weekly monthly short-term experiments in the absence of strong TIWs (Moum et al, 2022), implying that TIWs may have a minimal impact on long-term averages.…”
Section: Variability Of Individual Tiws and Relationship With Climate...supporting
confidence: 89%
“…TIW occurrence also exhibits interannual variability: In the Pacific, TIWs are generated more frequently during La Niña and less frequently during El Niño (An, 2008;Imada & Kimoto, 2012;Wu & Bowman, 2007a;Yu & Liu, 2003). In the Atlantic, variability has been attributed to the Atlantic Niña and Atlantic Niño (Olivier et al, 2020;Perez et al, 2012;Tuchen et al, 2024;Tuchen, Perez, et al, 2022;Wu & Bowman, 2007a). To mostly account for seasonal variability, discussion in Sections 4.1 and 4.2 focuses on observations exclusively from the TIW active seasons shown in Figure 3, when properties varied by a smaller amount.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, near-surface geostrophic velocity data, estimated at 15 m depth from a synthesis product of surface drifting buoy velocities and satellite-derived velocities from sea level anomalies and wind stress, are utilized to determine annual subduction rates (Lumpkin & Garzoli, 2011;Tuchen et al, 2022c). The latest version of this product is available annually from 1993 to 2021 and at 0.25°× 0.25°spatial resolution (Tuchen et al, 2024). For consistency with the other products, we use the data of the time period of 2007-2021.…”
Section: Near-surface Velocity Datamentioning
confidence: 99%